Quality of Citizen Reporting Tools at Municipal Level - Kopáčková, Hana; Líbalová, Petra (Modestum, 2019)
Quality of life in cities is highly dependent on the state of public infrastructure. Maintenance of the infrastructure is managed by the local government that needs to be informed about issues on the infrastructure. Although the duty of maintenance staff is to check the state of the infrastructure, it is difficult to know about all the problems in the city. Therefore, citizens can take the initiative and participate by reporting any issue on public infrastructure. Today, citizens have many options on how to report such issues, due to modern communication technologies. Citizen reporting systems, which are a special type of participatory technology, deserve deeper research due to its novelty in the information system research. In this article, we introduce the study of 13 Czech regional capitals and their reporting systems. In this study, we evaluate the existence of different types of communication channels (phone, e-mail, electronic form, WebGis, and mobile application) and their quality based on four criteria (searchability, coverage of issues, visual geolocation, and display of sent reports). Moreover, the results of regional capitals will be compared with previous research on cities in these regions.
Kvalita nástrojů hlášení závad na úrovni obcí
Keywords: citizen reporting; smart cities; non-emergency; e-participation; hlášení závad; chytrá města; non-emergency; e-participace